A porous framework based on tetrakis(4-pyridyloxymethyl)methane fine-tuned by metal ions: synthesis, crystal structures and adsorption properties. (11th December 2015) - Li, Zhao; Chen, Xi; Yu, Fan; Su, Min; Zhang, Bi-quan; Li, Bao; Zhang, Tian-le
Abstract : Solvothermal reactions of tetrakis(4-pyridyloxymethyl)methane and 4, 4′-oxybisbenzoic acid with different metal ions produced three new coordination polymers. Abstract : Solvothermal reactions of tetrakis(4-pyridyloxymethyl)methane (TPOM) and 4, 4′-oxybisbenzoic acid (H2 oba) with different metal ions under different synthesis temperatures produced three new coordination polymers (CPs), namely, [Co2 (TPOM)(oba)2 (H2 O)2 ] n (1 ), [Zn2 (TPOM)(oba)2 ] n (2 ) and [Cd2 (TPOM)(oba)2 (H2 O)2 ] n (3 ).1 and3 present similar topological structures which can be analyzed in two different ways.2 exhibits a rare porous structure assembled by the tetra-pyridinate ligand TPOM. The luminescence properties of2 and3 as well as those of the corresponding samples immersed in different solvents have been investigated, and they suggested a potential application in luminescence sensing. In addition, the dye and iodine adsorption properties of an activated sample of2 were also investigated. All of the results indicate that the proper selection of metal ions and auxiliary ligands plays an important role in constructing porous coordination polymers.